RE-INTERPRETASI BUDAYA BALI PADA MURAL DI LAPANGAN ASTAGINA PADANGSAMBIAN KLOD KOTA DENPASAR - Ni Kadek Yuni Utami; Ni Made Sri Wahyuni Trisna (LPPM Institut Desain dan Bisnis Bali, 2020)
The purpose of this report is to provide an overview of the preparation and implementation of Community Service activities at the Bali Institute of Design and Business in making murals at the Astagina Padangsambian Klod Denpasar field. The benefit of this report is that it provides an overview of the process of preparing and working on a mural as a form of cultural re-interpretation which also supports the vision and mission of Denpasar City as a cultural-minded creative city. The method used in the process and work of this Community Service is to prepare designs inspired by Balinese culture such as kite, congklak, tajog, Barong dance, etc. which are then visualized through a mural with a flat design with attractive colors. The results of the Community Service activities through the reinterpretation of Balinese culture on the mural at Astagina Field, Padangsambian Klod, give a new color to the Astagina field walls as well as provide cultural education to the local community and the general public.